Book Reviews (Journal of Finance, 1982)
Book reviewed in this article: Public Policy and Capital Formation . Savings and Loan Asset Management Under Deregulation: Proceedings . The Plight of the Thrift Institutions . By ANDREW S. CARRON Modern Portfolio Theory and Investment Analysis . By E. J. ELTON and M. J. GRUBER Investment Analysis and Management . By STANLEY HUANG Contemporary Financial Management . By R. CHARLES MOYER, JAMES R. McGUIGAN, and WILLIAM J. KRETLOW. St. Paul Planning Models for Colleges and Universities . By DAVID S. P. HOPKINS AND WILLIAM F. MASSY